1982
DOI: 10.1073/pnas.79.9.2822
|View full text |Cite
|
Sign up to set email alerts
|

Control of insulin receptor level in 3T3 cells: effect of insulin-induced down-regulation and dexamethasone-induced up-regulation on rate of receptor inactivation.

Abstract: Chronic exposure of 3T3 mouse fibroblasts to insulin or to the glucocorticoid dexamethasone induces down-regulation and up-regulation, respectively, of cell-surface and total cellular insulin binding capacity. Both processes are reversed upon withdrawal of the inducer. Scatchard analysis of insulin binding for receptors in the down-and up-regulated states indicates that the changes in binding capacity result primarily from alterations in insulin receptor level. That these alterations in total receptor level ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 25 publications
4
32
0
Order By: Relevance
“…Consistent with earlier reports (Fantus et al 1982, Knutson et al 1982, McDonald & Goldfine 1988, we have found an increase in the content of IRb in both cell lines in response to dexamethasone treatment. This prompted us to extend our studies in order to check whether the above glucocorticoid may have any impact on insulin signaling in BMOV-treated cells with depleted IRb level.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Consistent with earlier reports (Fantus et al 1982, Knutson et al 1982, McDonald & Goldfine 1988, we have found an increase in the content of IRb in both cell lines in response to dexamethasone treatment. This prompted us to extend our studies in order to check whether the above glucocorticoid may have any impact on insulin signaling in BMOV-treated cells with depleted IRb level.…”
Section: Discussionsupporting
confidence: 82%
“…In order to judge this probability, dexamethasone was chosen in our experiment to be co-administered with BMOV because the former drug is known to augment the transcription of IR gene and synthesis of IR in IM9 cells (Fantus et al 1982, McDonald & Goldfine 1988, and result in time-and dose-dependent increase in IR protein in mouse 3T3-C2 fibroblasts (Knutson et al 1982). This is also further confirmed by our study where the total cellular IRb content was increased in response to dexamethasone treatment, almost in a dose-dependent manner in 3T3-L1 cells revealing 41% augmentation at 10 mM drug (Fig.…”
Section: Effect Of Dexamethasone On Bmov-modulated Upstream Insulin Smentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by Fantus et al (1981) and Knutson et al (1982). The latter (Knutson et al, 1982) showed that an increase in the number of insulin binding sites with dexamethasone was due to a decrease in the degradation rate of insulin receptors. Furthermore, dexamethasone changed preadipocytes to adipocytes, accompained by an increase in the number of insulin receptors while changing the affinity for insulin (Rubin et al, 1978).…”
Section: Discussionsupporting
confidence: 79%
“…We know "down-regulation", in which the number of insulin receptors decreases with insulin treatment (Gavin et al, 1974 ;Blackard et al, 1978 ;Livingston et al, 1978 ;Petersen et al, 1978), and "upregulation", in which the number of insulin receptors increases with gulcocorticoid treatment (Fantus et al, 1981 ;Knutson et al, 1982), to regulate insulin receptors. Recently, Stevens et al (1983) showed that insulin increased its binding sites in cultured chondrosarcoma chondrocytes.…”
mentioning
confidence: 99%